(untitled) (Altre Modernità, 2011)
The aim of this paper is to explore two biblical plays written by André Gide between 1898 and 1902, namely "Bethsabé" and "Saül". A particular attention will be devoted to the second drama, mostly to its complicate hero, King Saul. The strong connection between these works and the literary figure of André Gide will be also hightlighted.